Changes in aerobic power and swimming economy as a result of reduced training volume - D'Acquisto, L. J.; Bone, M.; Takahashi, S.; Langhans, G.; Barzdukas, A. P.; Troup, J. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
This investigation examined the metabolic changes for submaximal and maximal swim efforts during a period of reduced training volume(taper). Well trained high school swimmers were assigned to one of two groups: GPl (n = 7) and GP2 (n = 6) averaged 32 000 and 64 000 metres/week, respectively, for the month preceding the study. The GPl did not experience a reduction in training volume until wk3 and wk4, whereas GP2 decreased their volume on a weekly basis for four weeks. Subjects were tested pre- (P), mid- (M and post-study (PT). Both GPl and GP2 were able to maintain aerobic power (l 0 /min) (P < 0.05) and improve performance (100 m and 200 m) (P < o.osj despite an approximate 65% (wk2 vs wk4) and 90% (P-wk4) reduction in training volume, respectively. The aerobic demand (ml 02 /min/kg) for four submaximal efforts decreased (P < 0.05) following the respective tapers. Greatest shift in economy occurred between M and PT for GPl, P and M for GP2. In conclusion: (1) a taper regimen which reduced training volume and maintained previous intensity and frequency resulted in enhancement of performance, no deterioration of aerobic power and improved economy (2) the 2 wk taper was similar in effectiveness to the 4 wk taper.